How does asymmetric sibling rivalry respond under environmental metal pollution? A case study of the Tree Sparrow (Passer montanus) - Jian Ding; Shengnan Wang; Wenzhi Yang; Huijie Zhang; Ni Wang; Yingmei Zhang (Avian Research)
The imbalanced allocation of maternal resources to eggs and nestlings may significantly impact the phenotype and fitness of offspring. Moreover, anthropogenic metal pollution has been reported to exert adverse effects on avian offspring. Therefore, we herein evaluated the relationships among offspring characteristics, asymmetric sibling rivalry, and the resulting offspring phenotype in a small passerine bird, Tree Sparrow (Passer montanus), at a polluted site (Baiyin, BY) and a relatively unpolluted site (Liujiaxia, LJX). By initiating incubation before the completion of clutch, asymmetric sibling rivalry might create a core and marginal offspring within the brood. In this study, lower egg mass, fewer core offspring, and more marginal offspring were found at the polluted site. Although eggshell speckling and coloration were relatively similar between the two sites, higher eggshell spotting coverage ratio and lower eggshell lightness (L∗) and hue (h°) were observed in core eggs than in marginal eggs at the unpolluted site. The clutch size had a positive relationship with egg mass at the polluted site and with brood size at hatching at the unpolluted site. The differences in egg measurements across the laying orders in the samples were relatively large for larger clutch sizes. The core and marginal egg masses had a significant positive effect on the size of early core nestlings and late marginal nestlings at the unpolluted site. Fledgling rate was significantly positively related to the incubation period and nestling period, while negative relationship with mean spotting coverage ratio was found at the polluted site. Marginal nestlings at the polluted site showed a higher mortality rate. Overall, although asymmetric sibling competition strongly determines the variation of marginal offspring size, the effect is less dramatic in metal-polluted environments, providing some respite to wild birds that survive pollution-induced stress.